Promoting developmental assets in positive youth development: identity development process through youth leadership mentoring in Malaysia - Arshad, Mohd Mursyid; Ismail, Ismi Arif; Che Nawi, Nur Raihan; Nawab Zadah Khan, Nasreen Khanum (Human Resource Management Academic Research Society, 2019)
Involvement in leadership activities is one of the approaches that enhances Positive Youth Development (PYD) among youths. The focus on mentoring process in a leadership program serves as the basis for developing these positive youth elements and has the potential to increase youth's readiness to lead Youth leadership development is a primary focus in Malaysia’s development agenda as outlined in the Malaysia Youth Policy (2015) and Youth Societies and Youth Development Act 668 (2019). Research and practice concur that the involvement of young leaders can be strengthened through wider exposure and professional training through mentoring. Mentoring offers a unique learning process that has been shown to enhance youth development outcomes and strengthening competence of youth leaders. The study was conducted to explore the identity development process in promoting developmental assets through the youth leadership mentoring. The study was conducted using a qualitative approach informed by the case study paradigm that involved 13 informants through in-depth interview data collection, participant observation and document analysis. Empirical findings from the study show that identity development resulted from the mentoring process through the value of tolerance, promotes empathy and shaping philanthropy spirit among youth leaders. In conclusion, data indicated that mentoring clearly has the potential to constitute the process of identity building among youth, and this process contributes to the development of their leadership capacities.